Antibody‐Incorporated Nanomedicines for Cancer Therapy - Wu, Shun‐Yu; Wu, Fu‐Gen; Chen, Xiaoyuan (Advanced materials (Weinheim), 2022)
Antibody‐based cancer therapy, one of the most significant therapeutic strategies, has achieved considerable success and progress over the past decades. Nevertheless, obstacles including limited tumor penetration, short circulation half‐lives, undesired immunogenicity, and off‐target side effects remain to be overcome for the antibody‐based cancer treatment. Owing to the rapid development of nanotechnology, antibody‐containing nanomedicines that have been extensively explored to overcome these obstacles have already demonstrated enhanced anticancer efficacy and clinical translation potential. This review intends to offer an overview of the advancements of antibody‐incorporated nanoparticulate systems in cancer treatment, together with the nontrivial challenges faced by these next‐generation nanomedicines. Diverse strategies of antibody immobilization, formats of antibodies, types of cancer‐associated antigens, and anticancer mechanisms of antibody‐containing nanomedicines are provided and discussed in this review, with an emphasis on the latest applications. The current limitations and future research directions on antibody‐containing nanomedicines are also discussed from different perspectives to provide new insights into the construction of anticancer nanomedicines. A comprehensive review on the advancements of antibody‐incorporated nanomedicines for cancer therapy is offered. Diverse functionalization strategies, antibody formats, and cancer‐associated antigens are introduced and discussed, with an emphasis on their latest applications in antibody‐incorporated nanotherapeutics. The current limitations and future research directions on antibody‐containing nanomedicines are also proposed.